Effect of a Phytogenic Water Additive on Growth Performance, Blood Metabolites and Gene Expression of Amino Acid Transporters in Nursery Pigs Fed with Low-Protein/High-Carbohydrate Diets - Cedrick N. Shili; Mohammad Habibi; Julia Sutton; Jessie Barnes; Jacob Burch-Konda; Adel Pezeshki (Animals, 2021)
The objective of this study was to investigate the effect of a phytogenic water additive (PWA) on growth performance and underlying factors involved in pigs fed with low-protein (LP)/high-carbohydrate diets. Forty-eight weaned barrows were allotted to six treatments for 4 weeks: CON-NS, control (CON) diet-no PWA; CON-LS, CON diet-low dose PWA (4 mL/L); CON-HS, CON diet-high dose PWA (8 mL/L); LP-NS, LP diet-no PWA; LP-LS, LP diet-low dose PWA; LP-HS, LP diet-high dose PWA. Relative to CON-NS, pigs fed with CON-HS had increased average daily gain, body weight and serum calcium (Ca) and phosphorous (P) and had decreased mRNA abundance of solute carrier family 7 member 11 and solute carrier family 6 member 19 in jejunum. Compared to LP-NS, pigs fed with LP-HS had increased muscle lean%, decreased muscle fat%, decreased serum Ca and increased serum P. Compared to their NS counterparts, CON-LS, CON-HS, and LP-LS increased the concentration of plasma essential AA and those fed with CON-HS and LP-HS tended to reduce the abundance of the solute carrier family 7 member 1 transcript in skeletal muscle. Thus, PWA improved the performance of weaned pigs fed with protein-adequate diets likely through increased blood essential AA and affected the muscle composition when dietary protein was deficient.